Correction: Cartilage-inspired superelastic ultradurable graphene aerogels prepared by the selective gluing of intersheet joints. Issue 26 (21st June 2016) - Hong, Jin-Yong; Yun, Sol; Wie, Jeong Jae; Zhang, Xu; Dresselhaus, Mildred S.; Kong, Jing; Park, Ho Seok
Abstract : Correction for 'Cartilage-inspired superelastic ultradurable graphene aerogels prepared by the selective gluing of intersheet joints' by Jin-Yong Hong, et al., Nanoscale, 2016, DOI: 10.1039/c6nr01986b.